BEGAWI ADAT PEPADUN MARGA BUAY SELAGAI DI KECAMATAN SELAGAI LINGGA KABUPATEN LAMPUNG TENGAH - Liza Putri; Umi Hartati (Swarnadwipa, 2018)
Lampung culture has a variety of forms and cultural systems as well as Begawi Adat Pepadun which is still often held in Kampung Negeri Agung Kecamatan Selagai Lingga. Kecamatan Selagai Lingga is one of the few villages located in Lampung area and has a clan or kebuayan from Abung Siwo Migo consisting of nine kebuayan. Selagai Lingga Sub-district has a culture that we often call Selagai culture. In the village of Agung, there is some history of the formation of Begawi Adat brought by Raden Cakradinata the grandfather of Minak Riyo Laggai who is very meritorious in bringing traditional culture.Therefore it has cultural values contained from Begawi Adat. The purpose of this research is to know the process of ceremony Begawi Indigenous Pepadun arga buay Selagai and to know the conservation efforts conducted by the community residing in Kecamatan Selagai Lingga Central Lampung district. This type of research using qualitative research methods that is by conducting interviews, observations and documentation located in the village of Agung. Based on the results of the research, the ceremony Begawi Indigenous Pepadun Kebagai especially Kebagai people who are in the village of Agung District Selagai Lingga can be concluded that the preservation is done especially in the village of the Great as a process of efforts in preserving the customs of society Lampung. The results of this study can be used as a source of learning and refrensi for students and can facilitate in finding information, especially in Lampung society culture.